Pembelajaran Pancasila Berbasis Interaksi Teman Sebaya sebagai Strategi Pendidikan Karakter bagi Siswa Sekolah Dasar - Sukri Badaruddin; Aan Setiawan; Salsabila Salsabila; Nurhaliza Nurhaliza; Masni Masni; Riskawati Riskawati; Fediyatun Muntazarah; Andi Samsul Alam (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to examine how peer interaction can be effectively utilized to foster values of togetherness and social care within the context of Pancasila learning at the elementary education level, particularly in Class VI of MIN 2 Majene. The study adopts a descriptive qualitative method with a case study approach, focusing on an in-depth understanding of the role of peers in cultivating togetherness and social concern through Pancasila instruction in Class VI of MIN 2 Majene. Data were collected through observation, interviews, and documentation, and were analyzed using data triangulation techniques, which include data reduction, data presentation, and conclusion drawing. The findings indicate that peer interaction plays a central role in nurturing students’ values of togetherness and social care through Pancasila learning in Class VI of MIN 2 Majene. Activities such as group work, discussions, and educational games enable students to directly experience values such as cooperation, tolerance, and empathy within a supportive and engaging learning environment. Students feel more comfortable and motivated when learning alongside their peers, which accelerates the internalization of Pancasila values. However, teachers face challenges in optimizing this strategy due to time constraints imposed by curricular demands and limited opportunities for professional training.